Thermostable Protease Production By Aneurinibacillus Thermoaerophilus Mcw220, Isolated From A Hot Water Spring (Applied Biological Research, 2015)
A thermophilic bacterium Aneurinibacillus thermoaerophilus MCW220  producing extracellular thermostable protease was isolated from  Manikaran hot water spring, Himachal Pradesh (India). Till date there  is no report of thermostable protease production by any Aneurinibacillus  thermoaerophilus. The strain MCW220 was characterized morpho biochemically followed by sequencing of its 16S rRNA gene. BLASTn  search analysis of the sequence showed maximum identity with A.  thermoaerophilus L420-91 and the G + C content was 57.2%. The A.  thermoaerophilus MCW220 when quantitatively screened for protease activity showed maximum thermostable protease activity of 33.4 U L-1.  The optimum yield and maximum protease activity was achieved at 48 h  incubation, with pH 7.0 at 60ºC. The desired protein was precipitated  and purified from the crude extract by using ammonium sulfate (80%)  and Sephadex G-100 column. The procedure yielded 0.105 g protein  with 2.35 fold purification with a yield 54.16%. The molecular mass of  enzyme was found 45 kDa by SDS-PAGE. Purified protease showed  maximum enzyme activity within the pH range of 9.0-9.5 at 50oC and  possessed compatibility with various detergents which make it a  potential candidate for use in detergent industry.
Keywords: Aneurinibacillusthermoaerophilus; hot water spring; SDS PAGE; thermophile; thermostable protease; 16S rRNA